DIARY KEHIDUPAN DALAM KARYA SENI LKIS EKSPRESIONIS - NORA SUSANTI, Drs. Erfahmi,M.Sn, Yasrul Sami, S.Sn., M.Sn (Universitas Negeri Padang, 2015)
The purpose of final work is to explore stories or note in diary of life into the paper with the expressionist style. The embodiment of ideas or arts, the writer presents a self portrait as a subject matter that describes the contents of the diary. In the creation of the work,the writer uses oil on canvas with a palette knife strokes and tehniques using intense colors. The style that used by the writer is expressionist style that developed since the 20th century in Germany who tend to use striking colors and shapes began to be distored. the writer has been created 10 works that is: 1) It necessary pain, 2) Only me, 3) Silent noise, 4) Pain happy, 5) I have I keep, 6) Power, 7) Peace with my self, 8) Peace with self, 9) Happiness is simple, 10) Crowded.Kata Kunci : Diary Kehidupan, Seni Lukis, Ekspresionis